Employee well-being of Finnish criminal investigators – mixed methods approach. Issue 1 (17th December 2019) - Saari, Tiina; Ellonen, Noora; Vuorensyrjä, Matti
Abstract : Purpose: The purpose of this paper is to compare the employee well-being of police officers in different investigative groups. This paper analyses crime investigators' employee well-being from four perspectives: organisational commitment, job satisfaction, exhaustion and turnover intentions. Design/methodology/approach: The analysis is based on Finnish Police Personal Survey data ( n =6, 698), and qualitative and quantitative analysis methods are utilised. Findings: Significant differences between investigative groups were found, and the police officers working in short-term investigations had the lowest level of well-being. The qualitative results revealed the employee- and organisational-level reasons behind these attitudes. One major issue is the lack of meaningfulness in work as the respondents describe their jobs as boring and monotonous and report that they do not have the appropriate resources to do their work as well as they wish. Practical implications: To enhance the well-being of the investigators, police forces should improve the ways of leadership and invest more resources especially on short-term investigation to diminish the insecurity and ensure the quality and continuity of the work. Originality/value: Research on the well-being of police officers has mostly focused on officers conducting surveillance or emergency operations, and there is very little knowledge of the well-being of crime investigators. This research adds to the limited knowledge on employee well-being of crime investigators.